Sasuduk in the Marriage Customs of Lampung Saibatin According to Islamic Law (Study in Gedung Cahya Kuningan Village, Ngambur District, West Coast Regency) - Aryani, Mera; Hidayat, Eko; Al Arif, M. Yasin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
The tradition of sasuduk or hiyokh sumbai is a practice of providing assistance in Lampung Saibatin traditional marriage which is still preserved in Gedung Cahya Kuningan Village, Ngambur District, West Coast Regency. This research aims to analyze the process of implementing the sasuduk tradition and examine the view of Islamic law on this practice. The research uses a descriptive qualitative method with a field research approach through observation, interviews, and documentation. The research informants included traditional leaders, religious leaders, community leaders, and people who carried out the sasuduk tradition. The results of the study show that sasuduk is carried out through the provision of staple foodstuffs, cash, or livestock which are recorded in detail by special officers with a reciprocal return system. This tradition has become a social necessity with sanctions in the form of gossip from the community and not receiving assistance when holding their own celebrations. From the perspective of Islamic law, the essence of sasuduk as a form of helping in goodness is in accordance with Islamic teachings. However, the system of recording and obligation to repay that resembles debts and harsh social sanctions is contrary to the principles of sincerity and voluntariness in giving ingive taught by Islam. The tradition of sasuduk needs to be returned to the essence of sincere and voluntary gotong royong in order to be in line with Islamic values